Structure and optical properties of amorphous AsS3-WS3 3-WS 3 thin films prepared by spin-coating using mixed n-propylamine-based solutions of AsS3 3 glass and (NH4)2WS4 4 ) 2 WS 4 powder - Durčíková, Lenka; Jančálek, Jiří; Přikryl, Jan; Mistrík, Jan; Frumarová, Božena; Šlang, Stanislav; Provotorov, Pavel; Kolobov, Alexander V; Krbal, Miloš (Elsevier Science, 2024)
Engineering new chalcogenide solids improves the desired functionality of the materials and may open the way for new applications. Here we discuss the preparation of As x S 100-x amorphous thin films modified with WS3 3 by the sol-gel method. We show that the formation of homogeneous, transparent, and stable n-propylaminebased solutions by mixing 0.02M As x S 100-x and 0.02M (NH4)2WS4 4 ) 2 WS 4 solutions is feasible for the As content in the chalcogenide glass precursor x <= 25 at.%. Above this limit, rapid and massive precipitation occurs in the solutions. We further demonstrate the preparation of amorphous thin films along the pseudo-binary AsS3- 3- WS3 3 tie-line and provide information about the role of WS3 3 on optical properties and the structure of tungsten- based chalcogenide thin films. Due to a significant etching contrast between annealed AsS3-WS3 3 -WS 3 thin films at 70 and 240 degrees C, we propose tungsten-based chalcogenide thin films as a suitable platform for application in wet-lithography.
Struktura a optické vlastnosti amorfních tenkých vrstev AsS3-WS3 připravených rotačním nanášením ze směsných roztoků skla AsS3 a prášku (NH4)2WS4 na bázi n-propylaminu
Keywords: Thin films; Chalcogenides; WS 3; AsS3; Spin-coating; Optical properties; Structure; tenké vrstvy; chalkogenidy; WS3; AsS3; rotační nanášení; optické vlastnosti; struktura